(untitled) (International Journal of Engineering and Computer Science, 2014)
Cloud Storage is a new emerging technology in which users can outsource their data on cloud and access it remotely from anywhere, thus the user can be free from the burden of data storage and its maintenance. But it is true that the data outsourced on cloud storage is not under the possession of user, so there is always a risk of integrity of data. The Cloud Storage should be such that the user should store the data on cloud as they are storing data on local system without worrying about data integrity. So for this purpose an external third party auditor (TPA) is introduced which performs the task of public auditing and users can rely on TPA for security of outsourced data. TPA performs the auditing of data, but this should not bring new risk to user’s data security by checking the contents of data while performing auditing. In this paper, we propose a scheme privacy preserving public auditing which stores the user’s data securely on the cloud. The proposed scheme is highly efficient and provably secured against both cloud service providers and external third party auditor (TPA).